Clinical recommendations for cardiopulmonary exercise testing in children with respiratory diseases. (2nd July 2020) - Takken, Tim; Sonbahar Ulu, Hazal; Hulzebos, Erik H. J.
ABSTRACT: Introduction: Cardiopulmonary exercise testing (CPET) quantitates and qualitates the integrated physiological response of a person to incremental exercise and provides additional information compared to static lung function tests alone. Areas covered: This review covers rationale for the use of CPET parameters beyond the usual parameters like peak oxygen uptake and peak minute ventilation in children with respiratory disease. Expert opinion: CPET provides a wealth of data from rest, submaximal and maximal exercise and data during recovery from exercise. In this review, an interpretative approach is described for analyzing CPET data in children with respiratory disease.